IMIGRAN DAN PERANTAU YANG “GAGAL” DAN PULANG KAMPUNG: Sebuah Firman yang Membangkitkan dari Kitab Rut - John Mansford Prior (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2015)
This essay details how an “intuitive reading” of the Book of Ruth by a group of HIV carriers from Flores island, Indonesia, renewed their faith. The men caught the virus as economic migrants and then proceeded to give it to their wives on returning home sick. Rejected by family and by many members of the clergy, they have formed their own support group. Coming from the interior, most were not regular church goers before contacting the virus. Some years ago they began reading the Scriptures regularly once a month. They easily identified with Naomi and Ruth, with their failed migration, and with the tactics they were forced to use in order to survive on returning to Bethlehem. Members of the HIV support group, largely unsupported by the institutional Church or by their extended families, have discovered in reading the Bible together a liberating Word that has rekindled a deep personal faith in the God of compassion. Kata-kata kunci: HIV, perantau, migran, ODHA, Support Group, Syering, Kitab Suci, Rut.